DIVERSITAS VEGETASI DI KAWASAN KARST - Syahril Sabirin; Gusti Syeransyah Rudy; Susilawati Susilawati (Universitas Lambung Mangkurat, 2026)
The aim of this research is to identify the types of vegetation that make up the karst area in Uren Village, Halong District, Balangan Regency. The object of this research is the understory plants in the karst area of Uren Village, Halong District, Balangan Regency. Primary data for this study were obtained through field observations by creating single plots using the purposive sampling method, which was determined based on land cover using the Normalized Difference Vegetation Index (NDVI). The results of this research found a total of 26 types of understory plants, with the following species names: daun hampalas (Acrotema costatum), kaladi hijau (Alocasia micholitziana), rarangka (Aristolochia macrophylla), mamali (Asian copperleaf), bajakah (Spatholobus littoralis), pacing (Costus woodsonii), ambung (Crassocephalum crepidioides), hiring (Cyperus rotundus), benggala (Tragia involucrata), pucuk paku (Diplazium esculentum), lirik macan (Geoppertia bachemiana), patiti (Hedychium greenii), bilaran tapah (Ipomoea purpurea), jelatang (Laportea macrostachya), piduduk (Melastoma malabathricum), sambung rambat (Mikania micrantha), pakis (Deparia petersenii), pandan hutan (Pandanus tectorius), pohon kasai (Paullinia pinnata), malalong (Philodendron grandipes), kakaladian (Philodendron toshibae), sirih hutan (Piper aduncum), rawa putih (Clerodendrum thomsoniae), rotan (Calamus axillaris), paku cakar ayam (Selaginella umbrosa) and paku-pakuan (Thelypteris reticulata).